2018
DOI: 10.1111/vco.12433
|View full text |Cite
|
Sign up to set email alerts
|

Response rate to a single dose of vinblastine administered to dogs with treatment‐naive multicentric lymphoma

Abstract: Vincristine is included in vincristine, cyclophosphamide, doxorubicin and prednisone (CHOP) chemotherapy protocols, which are the gold-standard treatment for high-grade canine lymphoma. Vincristine can result in relatively high rates of gastrointestinal toxicity, whereas vinblastine is generally well tolerated and thus may represent an under-utilized and minimally toxic alternative to vincristine. Our objective was to determine the response rate and toxicity associated with a single dose of vinblastine adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
2
7
1
Order By: Relevance
“…Incidence of hospitalisation after chemotherapy varied from 0% to 24% of dogs in literature, 13,27,38,49,51–53,57,60–63,66–70,80,81 which is similar to our study with 23.9% dogs that were hospitalised. Treatment course modifications were performed in 40.0% of dogs in our study and is commonly reported in dogs undergoing chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Incidence of hospitalisation after chemotherapy varied from 0% to 24% of dogs in literature, 13,27,38,49,51–53,57,60–63,66–70,80,81 which is similar to our study with 23.9% dogs that were hospitalised. Treatment course modifications were performed in 40.0% of dogs in our study and is commonly reported in dogs undergoing chemotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…sAE were observed at least once in 32.3%, which is higher than the figures reported in most studies, varying between 0% and 22.2%. 4,5,13,22,38,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] Only a few studies described a high rate of sAE, between 25% and 71%. [71][72][73][74] The discordance between our results and data available in textbooks and peer-reviewed publications could be explained by several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, gastrointestinal adverse events were mild and self-limited in both groups. Similar findings were also described in previous studies [4,15,21,23].…”
Section: Discussionsupporting
confidence: 93%
“…In that study, dogs were treated with 2 mg/m² doses of VBL while a small subset of dogs were treated with 2.5 mg/m² doses of VBL. Dogs treated with a higher VBL dose had significantly improved response rates, suggesting that an increase in the VBL dose may improve efficacy in some cases [4].…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, three dogs received drug substitutions as a result of toxicity. Vinblastine was incorporated into the protocol of a single dog as a result of unacceptable GI toxicity to vincristine, despite the questionable efficacy of this agent in dogs with multicentric lymphoma 39,40 . Similarly, a single dog received chlorambucil following development of sterile hemorrhagic cystitis and a single dog received mitoxantrone following the diagnosis of sinus node dysfunction.…”
Section: Discussionmentioning
confidence: 99%